Professional Commitment and Work Performance of Public Elementary School Teachers - Romantico, Robelse (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study determined the level of professional commitment and work performance of public elementary school teachers in selected schools in Tanay District, Division of Rizal, during the School Year 2025–2026. Specifically, it examined teachers’ professional commitment in terms of delivery of instruction, assessment of learning, and community involvement, and its relationship with their work performance based on the Individual Performance Commitment and Review (IPCR) results for School Year 2024–2025.A descriptive survey research design complemented by documentary analysis was utilized. The respondents were 200 public elementary school teachers from ten selected schools in Tanay District, Rizal. Data were gathered through a researcher-made questionnaire-checklist and supported by documentary analysis of IPCR ratings. Respondents were profiled according to age, sex, civil status, educational attainment, position title, length of service, and in-service trainings attended.Findings revealed that most teachers were 31 years old and above, female, married, and pursuing graduate studies. Many had served for more than 15 years and held Teacher I and Teacher II positions, with participation in division- and district-level trainings. Overall, teachers demonstrated a high level of professional commitment in instructional delivery, assessment practices, and community engagement. Their work performance was rated as very satisfactory based on IPCR results.Significant differences were found in professional commitment when grouped according to age, position title, length of service, and in-service trainings attended. However, no significant differences were observed in terms of sex, civil status, and educational attainment. Furthermore, a significant relationship was found between teachers’ professional commitment and their work performance.The study concludes that professional commitment is influenced by selected demographic and professional variables and is significantly associated with work performance. It is recommended that school administrators strengthen continuous professional development programs, while teachers enhance assessment strategies to improve learner outcomes. The proposed action plan is recommended for implementation, and further studies may explore additional variables.